Determination of Mangrove Adequacy as Natural Coastal Defence Against Wave Dynamics Using Remote Sensing Analysis for Southern Kedah Coastline - Mohammad Room, Fazira (Universiti Teknologi PETRONAS, 2017)
Malaysia had been hit by the Indian Ocean Tsunami (IOT) 2004 which has took 68 lives of Malaysia and thousands lives from the other affected countries. Kedah was one of the most affected states in northern Peninsular Malaysia. It is proved that less severe damaged found at area with presence of mangroves fringe on its coastline. It also has been proven by many researches on mangroves’ abilities in protecting the coastline by reducing the impact of the wave actions. However, if the Peninsular Malaysia is about to hit by tsunami again, it is unidentified if the current mangrove forest along the coastlines are able to reduce the impact of the tsunami’s waves just like how they did before. Therefore, this study aims to fully acknowledged and assess current condition of the mangrove forest along the Kedah’s coastline and evaluate their performances as the reliable natural coastal protector towards wave actions.